Theoretical and practice-oriented sociology, its virtual and real grounds - Levko, Anatoly I. (Journal of the Belarusian State University. Sociology, 2020)
In this article, the author distinguishes between practical sociology, the field of study of which is socio-cultural reality, and theoretical sociology, the subject of study of which is logical analysis of concepts and empirical facts. Positivist sociology, according to his opinion, deals not with the social reality itself, but with its modeling in the researcher’s thinking with the help of methods of various surveys, document analysis, social experiment. Practice-oriented sociology studies the following: socio-historical, socio-symbolic, anthropological and other cultural reality, in the study of which the decisive role belongs not to theory and logical analysis, but to experience of social interaction within a certain social space and time characterized by their inherent values and norms of behavior (historical epoch, national, territorial, settlement, gender and age, professional and other community). To form a realistic picture of crime in society, to reveal the causes of crisis in education, spiritual and moral degradation etc. from the position of their theoretical modeling, is impossible, according to the researcher. Its creation requires an appeal to the analysis of spiritual, symbolic, energy and other foundations of the development and functioning of society. The author traces the development of sociological science from medieval nominalism and realism to positivism of Auguste Conte, and from him to social logic and laws of imitation of Gabriel Tarde and social-cultural sociology of Emile Durkheim, from the religious and philosophical tradition of orthodox energetism and cosmism to social structuralism of Levi-Strauss and Michel Foucault, «habitus» by Pierre Bourdieu, symbolic interactionism of George Mead, theory of stigmatization, noospheric sociology, and a number of other research areas of Western European, American and domestic sociology.